Enhanced Efficiency and Mechanical Robustness of Flexible Perovskite Solar Cells by Using HPbI3 Additive. Issue 4 (17th February 2021) - Jiang, Nai-Rong; Wang, Yi-Fan; Dong, Qing-Feng; Ge, Cheng-Da; Yang, Zi-Qi; Yin, Da; Liu, Yue-Feng; Bi, Yan-Gang; Feng, Jing; Sun, Hong-Bo
Abstract : High efficiency and mechanical stability are in great demand for commercial applications of the flexible perovskite solar cells (PSCs) in portable and wearable electronics. Herein, power conversion efficiency (PCE) and mechanical robustness of the methylammonium (MA)‐free flexible PSCs are simultaneously enhanced by incorporating a HPbI3 additive with optimal content in the perovskite precursor solution. The HPbI3 additive facilitates an improved morphology and crystallinity, as well as a decreased work function of the perovskite films, leading to improved device performance. As a result, PCEs of 20.1% and 18.74% are obtained for the rigid and flexible PSCs, respectively, which are among the best results for inverted MA‐free PSCs. The flexible PSCs maintain 95% and 70% of the initial PCE value after 1000 and 5000 bending cycles, respectively, at a bending radius of 4 mm. The current result reveals that using the HPbI3 additive is a universal strategy to enhance performance of the flexible PSCs effectively and promote the development of the perovskite‐based photovoltaics. Abstract : Highly efficient and mechanically robust flexible perovskite solar cells (PSCs) are obtained by using an HPbI3 additive, which results in improved crystallinity and a decreased work function of the perovskite. The power conversion efficiencies (PCEs) of 20.1% and 18.74% are obtained for the PSCs on rigid and flexible substrates, respectively. The flexible PSCs maintain 70% of the original PCE after 5000 bending cycles.